2017
DOI: 10.19263/redia-100.17.10
|View full text |Cite
|
Sign up to set email alerts
|

Notes on Life-History of Erycia Furibunda (Diptera Tachinidae), a Parasitoid of Euphydryas Aurinia Provincialis (Lepidoptera Nymphalidae)

Abstract: In this paper we present new data on the larval-pupal parasitoid Erycia furibunda found in association with coexisting populations of E. aurinia provincialis in Central Italy. For the first time we provide information on the biology of this tachinid revealing the duration of puparium stage, the protandry and adult phenology in captive conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In the context of an ongoing study on the biology of butterfly endangered species (PINZARI, 2016a(PINZARI, , 2019aPINZARI et al, 2017PINZARI et al, , 2019 and Lepidoptera fauna in Italy (PINZARI, 2016b(PINZARI, , 2019b(PINZARI, , 2020PINZARI et al, 2018;PINZARI & PINZARI, 2019a, 2019b, 2019c we focused our attention on little-known species in central Italy.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of an ongoing study on the biology of butterfly endangered species (PINZARI, 2016a(PINZARI, , 2019aPINZARI et al, 2017PINZARI et al, , 2019 and Lepidoptera fauna in Italy (PINZARI, 2016b(PINZARI, , 2019b(PINZARI, , 2020PINZARI et al, 2018;PINZARI & PINZARI, 2019a, 2019b, 2019c we focused our attention on little-known species in central Italy.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of an ongoing study on Lepidoptera fauna in Latium, research has been carried out for many years and showed how much the fauna (PINZARI, 2016a;PINZARI, 2018b;, 2019c and biology (PINZARI & SBORDONI, 2013;PINZARI, 2016bPINZARI et al, 2017PINZARI et al, , 2018a (LVOVSKY et al, 2016); E. gerasimovi (Lvovsky, 1984) in Russia and eastern palearctic; E. icterinella (Mann, 1867) in Bulgaria, Croatia, former Jugoslavia, Cyprus, Greek mainland, Kriti and Near East (LVOVSKY et al, 2016); E. mercedella (Staudinger, 1859) in Portugal and Spain; E. mikkolai (Lvovsky, 1995) in Spain and North Africa (VIVES MORENO, 2003).…”
Section: Introductionmentioning
confidence: 99%